2010
DOI: 10.3892/ijo_00000828
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-transfected human umbilical cord blood-derived mesenchymal stem cells exhibit enhanced migratory capacity toward gliomas

Abstract: Abstract. Mesenchymal stem cells (MSCs) can be used as a delivery vehicle for gene therapy against brain tumors, because these cells have a migratory capacity toward glioma cells. Soluble factors including chemokines or growth factors expressed and released by glioma cells mediate the tropism of MSCs for gliomas. Among them, stromal cell-derived factor-1· (SDF-1·) has been identified as a key molecule related to the tropism of MSC in many cancers containing gliomas. In this study, we found that overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This can be improved by in vivo experiment using imaging to demonstrate whether this priming attracts more MSCs to the tumors. However, there is a large amount of evidence showing that increased CXCR4 expression on cell surface can promote tumor tropism in vivo [ 31 , 39 , 40 ], and efforts were also made in the current study to minimize animal suffering and to reduce the number of animals used. These are the reasons why we did not conduct these animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This can be improved by in vivo experiment using imaging to demonstrate whether this priming attracts more MSCs to the tumors. However, there is a large amount of evidence showing that increased CXCR4 expression on cell surface can promote tumor tropism in vivo [ 31 , 39 , 40 ], and efforts were also made in the current study to minimize animal suffering and to reduce the number of animals used. These are the reasons why we did not conduct these animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Tabatabai et al [131] demonstrated that irradiation induces tumor satellite formation at 21 days after intracerebral implantation of glioma. Irradiation enhances the tropism of bone marrow-derived cells (BMDCs) and HPCs to the gliomas, the proliferation of HPCs, and the vasculogenesis of BMDCs [131,180,186]. During these processes, SDF-1α has been identified as a key molecule.…”
Section: Sdf-1α/cxcr4 Axis and Radio-/chemoresistance In Gliomamentioning
confidence: 99%